Sosialisasi Sertifikasi Halal Pada Produk Olahan Makanan Pada Kelompok Usaha Bersama Desa Cipacing Kabupaten Sumedang - Dedah Jubaedah; Vinna Sri Yuniarti (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Halal certification is the process of issuing a halal certificate, which is carried out through a series of inspection stages to ensure that the raw materials, production processes, and halal assurance system of a company's products meet the applicable standards. The absence of halal certification limits marketing opportunities, increases the risk of contamination with non-halal ingredients, and decreases consumer trust. Based on these conditions, this community service activity is carried out with the aim of increasing the understanding and awareness of micro-business actors regarding the importance of halal certification. The methods used include socializing the concept, urgency, and process of halal certification; providing technical assistance in meeting administrative requirements; and assisting with the halal certification process. The results of the activity show an increase in business actors' understanding of halal certification. A total of 12 micro-business owners who were previously uncertified agreed to participate in this program, and 10 of them successfully completed the creation of their Business Identification Number (NIB) and filled out the PTSP Sihalal form. The halal process assistance shows that the participants' business activities have met the requirements of the Halal Product Assurance. The recommendations and conclusions of the assistance results were submitted to the Halal Inspection Agency (LPH) and the Halal Product Assurance Implementing Agency (BPJPH), which were then processed by the MUI Fatwa Council for the issuance of halal certificates.